2023
DOI: 10.3390/molecules28031293
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic Analysis of Urinary Extracellular Vesicles for Biomarkers of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) accounts for the most common form of primary liver cancer cases and constitutes a major health problem worldwide. The diagnosis of HCC is still challenging due to the low sensitivity and specificity of the serum α-fetoprotein (AFP) diagnostic method. Extracellular vesicles (EVs) are heterogeneous populations of phospholipid bilayer-enclosed vesicles that can be found in many biological fluids, and have great potential as circulating biomarkers for biomarker discovery and disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Furthermore, it was shown that the abnormal glycosylation of EV membrane proteins holds potential as an effective noninvasive biomarker for HCC diagnosis ( Li et al, 2023 ). Lin J et al isolated EVs from HCC and adjacent liver tissues for miRNA-level sequencing.…”
Section: Evs Can Serve As Biomarkers For Hcc Diagnosismentioning
confidence: 99%
“…Furthermore, it was shown that the abnormal glycosylation of EV membrane proteins holds potential as an effective noninvasive biomarker for HCC diagnosis ( Li et al, 2023 ). Lin J et al isolated EVs from HCC and adjacent liver tissues for miRNA-level sequencing.…”
Section: Evs Can Serve As Biomarkers For Hcc Diagnosismentioning
confidence: 99%
“…These findings suggest that profiling serum exosomal N -glycome may yield novel insights into potential HCC biomarkers. Li et al identified 756 N -glycopeptides in urinary EVs and found that glycoproteins LG3BP, PIGR, and KNG1 are upregulated in HCC128 . Although this study had a small sample size and the candidate markers were not validated, this study highlights the promise of site-specific glycomics analysis in the quest for new noninvasive diagnostic markers.…”
Section: Ev Glycosylation In Cancersmentioning
confidence: 99%
“…In addition, sEVs also show great potential in medical applications. In addition to playing increasingly significant roles in disease biomarker screening, sEVs are also believed to serve as a novel drug delivery system with intrinsic abilities to pass the blood–brain barrier and exhibit excellent biocompatibility and stability . Extensive research has focused on how sEVs interact with their recipient cells, i.e., recognition by cell surface receptors for signal transduction without cargo delivery into recipient cells, release of contents by means of vesicle-cell membrane fusion, , and a more general way to pass through the cell membrane and travel to a final destination .…”
Section: Introductionmentioning
confidence: 99%